Exploring EFL Learners’ Pragmatic Competence in Asking for and Giving Permission - Shella Aulia Putri; Musiman Musiman (Media Antartika Indonesia, 2026)
This study aims to examine EFL learners’ pragmatic competence in using expressions of asking and giving permission. The research was carried out at MTs Muhammadiyah Sukarame, Bandar Lampung, involving 32 eighth-grade students. A descriptive qualitative approach was applied to describe students’ speaking performance during classroom activities. The data were obtained through classroom observation, particularly during speaking practices. The findings indicate that students still encounter several difficulties in using appropriate expressions. Most of them have limited vocabulary, low confidence, and difficulties in applying correct grammatical structures. Consequently, their utterances are often incomplete and poorly organized. Furthermore, many students feel hesitant and afraid of making mistakes when expressing their ideas. These results show that students’ pragmatic competence in asking and giving permission remains relatively low. It also highlights the importance of providing more interactive and communicative learning activities to support the development of students’ speaking skills.